2016
DOI: 10.3389/fmicb.2016.01187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the In vitro Activity of Five Antimicrobial Drugs against Staphylococcus pseudintermedius and Staphylococcus aureus Biofilms

Abstract: Resistance in canine pathogenic staphylococci is necessitating re-evaluation of the current antimicrobial treatments especially for biofilm-associated infections. Long, repeated treatments are often required to control such infections due to the tolerance of bacteria within the biofilm. To comply with the goal of better antibiotic stewardship in veterinary medicine, the efficacies of the available drugs need to be directly assessed on bacterial biofilms. We compared the activities of amoxicillin, cefalexin, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The efficacy of the magnetically activated GLM-Fe particles was compared to that of three conventional antibiotics: amoxicillin, clindamycin, and tetracycline. Here, mature biofilms of S. aureus and P. aeruginosa were exposed individually to concentrations of the respective antibiotics at and/or above the minimum inhibition concentrations (MIC) and 100× the therapeutic dose level, as previously determined. , It should be noted that P. aeruginosa is thought to be innately resistant to clindamycin and amoxicillin; however, for tetracycline it is susceptible at concentrations of ∼32 μg/mL. Here we tested at higher concentrations of 50 μg/mL and 5 mg/mL, to thoroughly compare the efficacy of the antibiotics compared to the GLM-Fe particles.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of the magnetically activated GLM-Fe particles was compared to that of three conventional antibiotics: amoxicillin, clindamycin, and tetracycline. Here, mature biofilms of S. aureus and P. aeruginosa were exposed individually to concentrations of the respective antibiotics at and/or above the minimum inhibition concentrations (MIC) and 100× the therapeutic dose level, as previously determined. , It should be noted that P. aeruginosa is thought to be innately resistant to clindamycin and amoxicillin; however, for tetracycline it is susceptible at concentrations of ∼32 μg/mL. Here we tested at higher concentrations of 50 μg/mL and 5 mg/mL, to thoroughly compare the efficacy of the antibiotics compared to the GLM-Fe particles.…”
Section: Resultsmentioning
confidence: 99%
“…28 Based on in vitro data, marbofloxacin seems more likely to prevent biofilm formation than amoxicillin, cefalexin, doxycycline and clindamycin. 36 Likewise, in humans, fluoroquinolones are considered to be effective in preventing biofilm formation on ureteral stents. 37 Our results were different, as all cats with persistent/recurrent UTI postoperatively received postoperative marbofloxacin, while the two cats in which antimicrobials were discontinued immediately postoperatively did not develop a UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Manuka EO concentrations of 7.8-800 times the MIC (0.1% w/v) inhibited formation of biofilms by 76.2%. The study of Ferran et al [35] showed the inhibitory effect of antibiotics such as marbofloxacin (0.00005% w/v), clindamycin (0.001% w/v), doxycycline (0.001% w/v), amoxicillin (0.002% w/v) and cefalexin (0.005% w/v) against S. pseudintermedius biofilms was 1.2-1.4 times lower than that against planktonic cells.…”
Section: Biofilm Eradication Activitymentioning
confidence: 99%